The Problem of Being in the Philosophy of Pre-Socratists - Jankauskas, Skirmantas (Problemos, 1987)
The ancient philosophy presented by itself the way of self-realisation of the characteristic ancient man – the sage observer. This explains why the first ancient philosophers have interpreted their thinking as the way of practical (material) activity. The former circumstances predetermined the universal ontological orientation of the ancient philosophy, the latter – its original cosmological solution of the problem of existence. To the extent in which the antique philosophers became aware of the specific character of their activity, i.e., thinking, the twofoldness of their thinking began to manifest itself. This circumstance generated in the early ancient philosophy the inner contradiction, which on its turn put an end to the cosmological research.